2018
DOI: 10.36911/pannmed.v11i3.106
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Dan Sikap Pasien Gagal Ginjal Kronik (Ggk) Dengan Kepatuhan Dalam Menjalani Terapi Hemodialisa Di Ruangan Hemodialisa Rsup Haji Adam Malik Medan Tahun 2014

Abstract: Kasus gagal ginjal kronik di dunia meningkat, saat ini meningkat lebih dari 50% dari 6.840.507.003 miliar warga dunia. Tanpa pengendalian yang cepat dan tepat kemungkinan tahun 2015 jumlah pasien yang menbutuhkan cuci darah diperkirakan 36 juta penduduk dunia. Penderita gagal ginjal kronik Di Amerika Serikat setip tahun ada sekitar 20 juta orang dewasa menderita penyakit ginjal kronik, dan harus melakukan hemodialisa (Seoleman, 2008). Penelitian ini bertujuan untuk mendapatkan gambaran umum tentang Hubungan pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, compliance with fluid restrictions is a very important factor in determining the level of well-being of patients on hemodialysis (Karyati, Sukarmin and Listyaninsih, 2019). One of the factors that influences compliance is attitude, attitude is a willingness to act that is not based on certain motives (Soep, 2017). Apart from that, in research conducted by Saraswati et al (2019) concluded that there is a significant relationship between family support and compliance with fluid restrictions.…”
Section: Santa Manurung Et Al the Relationship Between Attitudes And ...mentioning
confidence: 99%
“…Therefore, compliance with fluid restrictions is a very important factor in determining the level of well-being of patients on hemodialysis (Karyati, Sukarmin and Listyaninsih, 2019). One of the factors that influences compliance is attitude, attitude is a willingness to act that is not based on certain motives (Soep, 2017). Apart from that, in research conducted by Saraswati et al (2019) concluded that there is a significant relationship between family support and compliance with fluid restrictions.…”
Section: Santa Manurung Et Al the Relationship Between Attitudes And ...mentioning
confidence: 99%